Keputusan Wisatawan berkunjung ke Objek Wisata Budaya di Kabupaten Tulang Bawang Barat Provinsi Lampung - muhammad saputra; Yusminar Wahyuningsih; Novita Sari; Bimo Wira Gayo (Fakultas Ekonomi Universitas Kadiri, 2024)
The purpose of this study is to determine tourist decision to visiting tourist destination in West Tulang Bawang regency Lampung Province effected of tourist attraction, brand destination, tourist event. This research focus on Uluan Nughik “Badui Homes” etnic city tourist destination. This study is asosiatif research. Total sample of this study taken by purposive sampling technique with 130 repondent used Hair formula. Data analysis in this study used smart PLS. The result of this study show tourist attraction variable influence tourist decision to visit. Brand destination influence tourist decision to visit. Tourist event influence tourist decision to visit.